Direct Evidence of the Benzylium and Tropylium Cations as the Two Long‐Lived Isomers of C7H7+. Issue 23 (11th October 2018) - Jusko, Pavol; Simon, Aude; Banhatti, Shreyak; Brünken, Sandra; Joblin, Christine
Abstract: Disentangling the isomeric structure of C7 H7 + is a longstanding experimental issue. We report here the full mid‐infrared vibrational spectrum of C7 H7 + tagged with Ne obtained with infrared‐predissociation spectroscopy at 10 K. Saturation depletion measurements were used to assign the contribution of benzylium and tropylium isomers and demonstrate that no other isomer is involved. Recorded spectral features compare well with density functional theory calculations. This opens perspectives for a better understanding and control of the formation paths leading to either tropylium or benzylium ions. Abstract : C7 H7 + isomers : by using infrared pre‐dissociation spectroscopy and saturation depletion measurements of C7 H7 + ⋅ Ne complexes, we demonstrate that benzylium and tropylium cations are the only two long‐lived isomers of gas‐phase C7 H7 + .